2020
DOI: 10.2147/cmar.s257727
|View full text |Cite
|
Sign up to set email alerts
|

<p>Elevated Platelet Count Predicts Poor Prognosis in Breast Cancer Patients with Supraclavicular Lymph Node Metastasis</p>

Abstract: Background: More and more studies show that platelets are closely related to the occurrence and development of tumors. This study aims to explore the predictive value of peripheral blood platelet count on the prognosis of breast cancer patients with ipsilateral supraclavicular lymph node (ISLN) metastasis. Methods: Eighty-five breast cancer patients with ISLN metastasis in the Affiliated Cancer Hospital of Zhengzhou University were collected retrospectively in this study. Chi-square test was used to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…In glioblastoma, an increase in platelet count was previously assumed to be an unfavorable prognostic feature [41]. This fits with the experience in most solid tumors that the elevated platelet count plays a critical role in progression and metastasis [42][43][44]. Presumed mechanisms include protecting circulating tumor cells from attacking the host's immune system as well as supporting proliferation of tumor cells [45].…”
Section: Discussionsupporting
confidence: 68%
“…In glioblastoma, an increase in platelet count was previously assumed to be an unfavorable prognostic feature [41]. This fits with the experience in most solid tumors that the elevated platelet count plays a critical role in progression and metastasis [42][43][44]. Presumed mechanisms include protecting circulating tumor cells from attacking the host's immune system as well as supporting proliferation of tumor cells [45].…”
Section: Discussionsupporting
confidence: 68%
“…The current study found that platelet count was significantly increased before and after treatment, with a significant increase between the zero cycle and the fourth cycle, and between the fourth and the eighth cycle. This can be due to cancer cells’ ability to cause thrombocytosis and platelet aggregation [ 28 30 ]. Moreover, thrombocytopenia in the current study before treatment was 6.3% (95% CI: 3.3, 10.5) and after treatment was 8% (95% CI: 3.7, 12.3).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, low MPV and high platelet counts were both associated with poor COS outcomes. Although no previous study had examined the relationship of MPV or the platelet count with COS outcomes, low MPV or high platelet count had been reported to be associated with a poor prognosis and metastasis in patients with breast cancer ( 30 , 31 ). MPV indicates the platelet size, and an increase in this value is an indicator of a large number of reactive platelets resulting from increased platelet turnover.…”
Section: Discussionmentioning
confidence: 99%